Analysis of Economic Potentials of Products Effort to Reduce Inter-District Institutions in Tegal Regency - Mulyo Sugiarto (EKO-REGIONAL, 2018)
This study aims to analyze the economic potential to reduce inequality between sub-districts in Tegal Regency. The result of the research shows that with mapping analysis of production modification of each sub-district which has a fast growing potential economic sector and contributing significantly in Tegal Regency during the period of 2009-2013 a) The superior agricultural sector in Sub Distric Balapulang, Suradadi, Warurejo; b) Superior Mining and Quarrying Sector in Balapulang Sub District; c) Superior Processing Industry Sector in Sub Distric Pangkah, Slawi, Adiwerna, Warurejo; d) High Electricity, Gas and Water Sector in Slawi, Dukuhwaru, Dukuhturi Sub-District; e) Superior Building Sector in Kecamatan Pangkah, Slawi, Dukuhwaru, Kramat, and Warurejo; F) Superior Trade, Hotel and Restaurant Sector in Jatinegara and Adiwerna Sub-district; g) The Transport and Communications Sectors excel in Margasari, Bojong and Pagerbarang Sub-districts; h) The Finance, Leasing, and Corporate Services sector is superior in Margasari, Balapulang, Pangkah Sub Distric; i) superior service sectors in Pangkah, Slawi, Adiwerna, and Suradadi Sub Distric.Keywords: Regional Inequality, Economic Potential, Base Sector, Relative GRDP Growth, Klassen Typology.